A Comparison of the Quasi-Steady Assumption with Unsteady Effects on Tower Galloping Analysis - Zihang Yang; Yangzhao Liu; Ying Chang; Kaoshan Dai (Buildings)
Traditional tower galloping theory is founded on the quasi-steady assumption, which has inherent limitations. By treating tower galloping as a single-degree-of-freedom crosswind bending flutter problem and introducing flutter derivatives into the expression of the crosswind aerodynamic force acting on the tower, the unsteady effects induced by motion can be incorporated into the analysis of tower galloping. An actual chamfered square cross-section tower was used as the research subject, and static tests and flutter derivative identification tests were performed on tower segment models without any modifications and with two types of aerodynamic measures: added arc-shaped fairings and vertical fin plates. Predictions of the aerodynamic damping of the tower structure were made and compared based on two different galloping theories: one under the quasi-steady assumption and the other considering unsteady effects. Experimental results indicate that both theories lead to the same conclusion about the galloping stability of the chamfered square tower. The original cross-section tower exhibited significant galloping instability problems, but the addition of arc-shaped fairings or vertical fin plates effectively improved its galloping stability performance. The predicted results of the tower’s aerodynamic damping based on the two different galloping theories differed by at most 34% at dimensionless wind speeds below 25. However, some differences were observed, and these differences between the two theories were noticeably affected by the magnitude of the dimensionless wind speed.